James Madison - Wills, Garry, 1934- (New York : Times Books, 2002)
In this examination of the life of a founding father, renowned historian Wills takes a fresh look at the life of James Madison, from his rise to prominence in the colonies through his role in the creation of the Articles of Confederation and the first Constitutional Congress.
1. Pre-presidential years (1751-1809) -- 1. Before the Constitution -- 2. The Constitution -- 3. Three administrations -- 2. The Presidency : first term (1809-1813) -- 4. Policy and personnel -- 5. Domestic affairs : the partisans -- 6. Foreign affairs : suckered twice -- 7. Maneuvering into war -- 8. To conquer Canada -- 9. Frigates and a fresh start -- 3. The Presidency : second term (1813-1817) -- 10. Peace overtures and professionalism -- 11. Washington and Baltimore -- 12. Maneuvering out of war -- 13. Assessing the Presidency.
Includes bibliographical references (p. [173]-174) and index.
Keywords: Madison, James, -- 1751-1836.; Presidents -- United States -- Biography; United States -- Politics and government -- 1809-1817.